ROAD SAFETY EDUCATION IN A PEDIATRIC UNIT - Ana Cristina Geiss Casarolli; Franciele Foschiera Camboin; Solânia Durman; Claudia Brandelero Rizzi (Universidade Federal do Paraná, 2013)
This descriptive-exploratory study aimed to evaluate the applicability of educational practice regarding road safety, through booklets with cartoon images and software. Educational activities were undertaken between November 2010 and February 2011, with 41 children and adolescents, following which an evaluative questionnaire was administered. Among the participants 37 (90.2%) reported not having difficulties in using the program, 40 (97.6%) did not find it difficult to participate in the activities, 27 (65.9%) did not need help, 35 (85.4%) found the activity colorful, 32 (78%) reported not having participated in another, similar, activity, and all managed to finish, and enjoy, the activity. The results show that educational practice, with the strategies used, was efficacious in sensitizing the child-adolescent population to safe behavior in traffic, and that the strategies can support other educational practices in this environment.